A Jack of All Trades—Tawaki/Fiordland penguins are able to utilise diverse marine habitats during winter migration - Mattern,Thomas; Pütz,Klemens; Borboroglu,Pablo Garcia; Ellenberg,Ursula; Houston,David M.; Lüthi,Bernhard; Seddon,Philip J. (PeerJ, 2025)
Migration and non-breeding movements are common across animal groups and are often driven by seasonal changes in habitat conditions. This behaviour is prevalent in crested penguins (Eudyptes sp.), which have evolved in and still primarily inhabit the subantarctic regions of the Southern Hemisphere. These species migrate outside the reproductive phase due to the limited year-round productivity around the breeding sites. Tawaki/Fiordland penguins (Eudyptes pachyrhynchus) are unusual in that they breed in temperate, continental New Zealand, an environment that appears productive enough to support year-round residency, yet they undertake extensive migrations during the non-breeding period. To investigate the drivers and patterns behind this behaviour, we used satellite telemetry to track 14 adult tawaki from across their breeding range during the winter of 2019. We examined whether migration routes differed by breeding location, and used maximum entropy (Maxent) modelling to identify environmental predictors of habitat use during the non-breeding period. All penguins followed a similar south-westerly trajectory toward the subantarctic waters south of Tasmania, irrespective of origin. Birds reached maximum distances of up to 2,193 km from their colonies, traveling a median total distance of 6,086 km over 135 days. Maxent models showed that mixed layer depth (i.e., the mixing height at the ocean surface) around 80 m was the strongest predictor of habitat suitability, aligning with known foraging depths in this species. Tawaki were associated with oceanic habitats ranging from polar to subtropical regions—a broader environmental range than other crested penguins, which tend to remain within a single water mass. These findings highlight the flexibility of tawaki in their use of marine habitats. This behavioural plasticity may suggest resilience to environmental variability, offering insights into why tawaki appear to be maintaining stable population trends while other New Zealand crested penguins are in decline.
Keywords: Penguins; Satellite tracking; Telemetry; Winter migration; New Zealand; Tawaki; Fiordland penguin